Gender Hegemony in Arabic Textbooks Endorsed by the Indonesian Ministry of Religious Affairs - Reflinaldi; Hadi, Syofyan; Rahmi, Awliya; Rezi, Melisa; Khairunnisa, Annisa (Institut Agama Islam Negeri (IAIN) Kendari, 2026)
Despite previous studies revealing the gender representation discrepancy in Arabic textbooks published by the Indonesian Ministry of Religious Affairs, no analysis has addressed the underlying reasons for this disparity. This study seeks to identify gender hegemony in the same textbooks toaddress this unresolved gap by investigating the forms of gender hegemony constructed. The study examines both linguistic and visual data drawn from seven thematic units across three Madrasah Aliyah Arabic textbooks (Grades X, XI, XII) published in 2020. Data were gathered through systematic re-transcription of narrative texts and structured digital archiving of images. Drawing on a gender-hegemony framework analysis, the research identified the existence of hegemonic masculinity and hegemonic femininity within the domains of family and home, jobs, hobbies, traveling, sports, and higher education, analyzed across seven materials at three educational levels. Both forms of gender hegemony are present in texts and images and are concurrently organized and systematized to establish male superiority and female inferiority. The presence of this hegemony is the principal cause of disproportionate gender representation. These findings extend the field beyond representational counting by offering a critical discursive account of why gender inequality persists in state-sanctioned Arabic learning materials. Theoretically, the study contributes a transferable dual-hegemony analytical model to multimodal critical discourse analysis. For educational policy, it provides an evidence base for systematic gender auditing of officially published instructional content in Indonesian Islamic schools.